Understanding the Risk of Homelessness for Emerging Adult Foster Care Youth : FCS3367/FY1506, 01/2022 - Michelini, Francesca; Cantrell, Randall; Fogarty, Kate (EDIS, 2022)
This publication discusses foster care in the United States, risk of experiencing homelessness among foster care youth, and possible interventions. Written by Francesca Michelini, Randall Cantrell, and Kate Fogarty, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2022.